Preventing marine wildlife crime: An evaluation of legal protection and enforcement perspectives - Nurse, Angus (Frontiers in Conservation Science, 2023)
Despite growing environmental awareness and the efforts of a variety of Non-Governmental Organisations (NGOs) to influence the wildlife protection policy agenda, wildlife laws remain outside the remit of mainstream criminal justice. The urban-centric focus of criminology is evident in regard to wildlife crime, which has received little focus in mainstream criminology. However, given the threat to the planet’s biodiversity and wide-scale harms that result from wildlife crimes, green criminology argues for wildlife crime as an important area of criminological inquiry. Green criminological perspectives contend that both wildlife crime and wildlife harms require greater attention in policy and enforcement discourse. This article considers wildlife crime in respect of threats to UK marine wildlife. It examines the UK’s legal and enforcement framework and the scope and nature of both marine wildlife crime and harms to marine wildlife. Acting from a green criminological perspective, the article examines the extent to which the UK’s wildlife law approach provides for effective wildlife protection and is adequate to deal with the threats facing marine wildlife. It considers the relevant law, case law and reporting of wildlife crimes as well as the enforcement approach to marine wildlife crime. The article identifies that in principle the UK has robust legal protection for marine wildlife. But in practice, policy allows exploitation and disturbance of marine wildlife that causes harm to individual animals and is detrimental to efforts to conserve marine wildlife and marine ecosystems. Accordingly, this article argues for marine wildlife crime to be integrated into mainstream crime policy linked to other forms of offending and criminal justice policy, rather than being largely seen as a purely environmental issue and a ‘fringe’ area of policing.